Trends in modern construction - Saviovskyi, V. (Ways to Improve Construction Efficiency, 2022)
The article highlights the results of analysis and systematization of certain trends in the development of modern construction in Europe and Ukraine. It is indicated on the main directions of increasing the efficiency of investments in construction due to the improvement of structural and organizational and technological solutions. It was established that one of the priority areas in construction is construction processes aimed at improving the thermal protective properties of buildings, namely, the device for heat insulation of external enclosing structures of walls, roofs, windows, and external doors. This area is key in domestic and European construction. According to statistics, more than 75% of existing civil buildings in Europe and more than 90% in Ukraine do not meet modern standards for energy conservation. The next direction of development of construction technologies indicates the introduction of prefabricated and prefabricated monolithic structures. The direction in construction, which was recently dominant in our country and over time partially neglected, is reviving again at a rapid pace, both in Europe and in Ukraine. Full-assembly and prefabricated monolithic structures and technologies make it possible to carry out relatively simple technological processes of erecting buildings on a construction site with structures of high factory readiness. This reduces the labor intensity of construction processes, improves the quality of work and does not require a high level of qualification of individual construction professions, such as an installer. One of the important areas of modern construction is the reconstruction of existing buildings and territories. The reconstruction of civilian buildings is aimed at restoring the operational properties of existing buildings with a possible superstructure, extension, reconstruction and their mandatory thermal modernization. These processes include disassembly of the roofs of low-rise buildings with their subsequent superstructure, extension of balconies, improvement of adjacent areas. These activities are aimed at extending the time frame and improving the conditions for the further operation of buildings. Also, the scope of work on the reconstruction of industrial buildings and territories for objects for civil, socio-cultural purposes, that is, their revitalization, is constantly expanding.